2021
DOI: 10.3389/fpsyg.2021.752026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Research on Art Therapy Indexed in the Web of Science: A Bibliometric Analysis

Abstract: Aim: Despite the increase in international research in art therapy, few studies have been developed with a bibliometric approach which describe the situation regarding this area of knowledge. Thus, the aim of this study is to describe and contextualize international scientific production in the visual arts modality in the context of artistic therapies, to offer a broader and more in-depth vision of the structure of this area of knowledge through of a bibliometric analysis of the publications indexed in the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It should be noted that the most commonly used forms of fine arts are drawing, painting, and photography. In the case of fine art in the form of drawing, illustration, painting, collage, photography, and sculpture, it is used not only as a tool for clinical intervention but also as a diagnostic tool, which gives fine art a universal and innovative character and distinguishes it from other modalities of art therapy (Novo et al, 2021). The essence of collage as an art therapy technique is to create images by combining various photographs, newspaper or magazine clippings, fabrics, coloured paper, wood, wire, and rope, which captivates and relaxes both a child and an adult.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the most commonly used forms of fine arts are drawing, painting, and photography. In the case of fine art in the form of drawing, illustration, painting, collage, photography, and sculpture, it is used not only as a tool for clinical intervention but also as a diagnostic tool, which gives fine art a universal and innovative character and distinguishes it from other modalities of art therapy (Novo et al, 2021). The essence of collage as an art therapy technique is to create images by combining various photographs, newspaper or magazine clippings, fabrics, coloured paper, wood, wire, and rope, which captivates and relaxes both a child and an adult.…”
Section: Resultsmentioning
confidence: 99%
“…Alanine aminotransferase acted as a mediator between PM 2.5 and HCC ( 29 ). On account of its tiny size, PM 2.5 can travel into the human body by respiration or ingestion and then have access to blood ( 8 ), suggesting that PM 2.5 exposure was significantly associated with several cancer-specific mortalities, including those of the oral cavity and nasopharynx, esophagus, stomach, colon rectum, liver, gallbladder, larynx, lung, bone, skin, female breast, cervix, prostate, brain, and leukemia ( 12 ). Therefore, “fine,” “human health,” and “air quality” were included.…”
Section: Discussionmentioning
confidence: 99%
“…The bibliometric analysis combined objective procedures like performance analysis with subjective ones such as thematic analysis to assess article performance, collaboration among authors, institutions, and countries, and recent research hotspots with future directions ( 12 ). Bibliometric software like VOSviewer, HistCite, CiteSpace, and Gephi makes the aforementioned analysis possible and effective; it is widely used in this field.…”
Section: Methodsmentioning
confidence: 99%
“…In another study examining a total of 563 works on art therapy in the visual arts, it was determined that painting, painting, and photography were the most used modalities in the field of visual arts for art therapy purposes. In these studies, it was concluded that art therapy had effects that improve rehabilitation and reduce psychological distress in patients [34]. Different clinical guidelines from the National Institute for Health and Care Excellence (NICE) include art therapy as an indication with recommended evidence.…”
Section: Health Promotion and Art Therapymentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) presents art therapy as an indication with evidence. Nursing Interventions Classification (NIC) has accepted art therapy as a nursing intervention since the beginning of the 21st century [34,35].…”
Section: Health Promotion and Art Therapymentioning
confidence: 99%